Impact of IFN-g gene polimorphism on the risk of cervical cancer - Kordi Tamandani, M.K.; Sobti, R.C.; Shekari, M.; Suri, V. (Experimental Oncology, 2008)
Cervical cancer, the second most common malignancy in women worldwide, is almost invariably associated with infection by human papillomavirus (HPV). However, although many women are infected with high-risk types of HPV, only a subset of infected women will ever develop cervical cancer. Several studies suggested that immunological components play a key role in the development of cervical cancer. Interferon gamma (IFN-g) is a cytokine produced by activated T cells and natural killer (NK) cells that enhances cellular immune responses by increasing T-cell cytotoxicity and NK cell activity. Aim: To study single nucleotide polymorphism (SNP), T to A, located at the +874 position and measure IFN-g messenger RNA (mRNA) at the tumor site. Methods: DNA was isolated from peripheral blood of 200 patients with cervical cancer and 200 healthy controls. The allele polymorphism at position +874 in the IFN-g gene was studied by ARMS-PCR (Amplification Refractory Mutation System) and measured IFN-g mRNA at the tumor site by means of a semi-quantitative polymerase chain reaction (sqRT-PCR) assay. Results: It was observed that genotypes AT and AA + AT increase the risk of cervical cancer (OR = 3.3, 95% CI — 2.05–5.2, P ≤ 0.001 — OR = 2.9, 95% CI — 1.9–4.6, P ≤ 0.001, respectively). In case of passive smokers same genotypes showed highly significant increased risk of cervical cancer (OR = 5.55, 95% CI = 2.77–11.19 — OR = 5.25, 95% CI = 2.77–10, respectively). Thus, the sqRT-PCR reflected the similar level of mRNA expression of IFN-g gene in patients suffering from cervical carcinoma and healthy controls. Conclusion: This is the first study to provide an evidence for effecting of IFN-g gene on the risk of cervical cancer in north Indian population. Рак шейки матки является второй по распространенности опухолью у женщин во всем мире, и почти неизменно ассоциирован
с инфицированием вирусом папилломы человека (HPV). Тем не менее, хотя многие женщины инфицированы HPV с
высоким риском развития рака шейки матки, только у некоторых из них развивается данное злокачественное заболевание.
Несколько проведенных ранее исследований показали, что иммунологические компоненты играют важную роль в развитии
рака шейки матки. Гамма-интерферон (IFN-γ) является цитокином, который продуцируется активированными Т-клетками
и естественными киллерными клетками (NK), что приводит к повышению эффективности клеточных иммунных ответов,
способствуя усилению цитотоксичности Т-клеток и активности NK-клеток. Цель: изучить одиночный нуклеотидный полиморфизм
(SNP), замену T на A в положении +874 и оценить уровень экспрессии РНК, кодирующей IFN-γ, в опухоли.
Методы: ДНК выделяли из периферической крови 200 больных раком шейки матки и 200 здоровых доноров. Аллельный
полиморфизм гена IFN-γ в положении +874 изучали с помощью ARMS-PCR (Amplification Refractory Mutation System).
Оценку количества кодирующей IFN-γ мРНК в опухоли проводили с помощью полуколичественной обратной полимеразной
реакции (sqRT-PCR). Результаты: показано, что генотипы AT и AA + AT повышают риск развития рака шейки матки (OR =
3,3; 95% CI — 2,05–5,2; P ≤ 0,001 — OR = 2,9; 95% CI — 1,9–4,6; P ≤ 0,001). В случае пассивных курильщиков при тех же
генотипах отмечено очень существенное повышение риска развития рака шейки матки (OR = 5,55; 95% CI = 2,77–11,19 —
OR = 5,25; 95% CI = 2,77–10). В то же время sqRT-PCR показал, что мРНК IFN-γ экспрессирована на одинаковом уровне
у больных раком шейки матки и у здоровых доноров. Выводы: проведено первое исследование, доказывающее вклад полиморфизма
гена IFN-γ в риск развития рака шейки матки у жительниц северной части Индии.